Formation of Practical Skills in Preparing Future Teachers of Physics (Journal of Educational Sciences, 2017)
The article shows the main methods used in higher education institutions in order to develop an interest in science among students in the natural sciences. Conducted practical work through the use of techniques by combining scientific research with the learning process, thereby increasing the quality of education and the development of scientific knowledge at the future teachers. The necessary knowledge and skills to improve the comprehensive development of abilities and interests, the formation of life values and attitudes of students. Particular attention is paid to the research work of students, in order to form research skills, self-solve practical problems, the ability to search and find a new one. Paying attention to the forms of teaching and research. The joint work of students and pupils promotes language acquisition techniques, the development of abilities and skills using a variety of tools, etc. The article raises the question, both from a theoretical and practical point of view, the problem of formation of practical skills of the future expert in general education. The importance of professional qualities of the specialist, as well as the need to attract graduates of pedagogical universities to work in the general education system.Key words: physics teacher, student activities, student experimental platform, research, physical phenomena.